Enhancing the competency of vocational students through 3D CAD training using Solidworks - Romiyadi Romiyadi; Widya Sinta Mustika; Yudi Dwianda; Adi Febrianton; Purnama Irwan; Indah Purnama Putri (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Computer-aided design (CAD) is one of the competencies taught to vocational students. The software commonly used is Auto CAD, which focuses on constructing two-dimensional (2D) drawings. AutoCAD can also create three-dimensional (3D) drawings, but its features are limited. Based on these conditions, through community service activities, Politeknik Kampar improves the competence of students of SMK Negeri 1 Bangkinang Kota, Department of Mechanical Engineering. This activity aims to strengthen the CAD competence of vocational students using Solidworks software. The results of the training activities show the level of success with indications of a positive response from the participants and the participant's understanding of the material being taught. Computer-aided design (CAD) merupakan salah satu kompetensi yang diajarkan kepada siswa smk. Software yang biasa digunakan adalah Auto CAD yang fokus pada konstruksi gambar dua dimensi (2D). AutoCAD juga dapat digunakan untuk membuat Gambar tiga dimesnsi (3D), tetapi fiturnya sangat terbatas. Berdasarkan kondisi tersebut, Politeknik Kampar turut serta dalam meningkatkan kompetensi siswa SMK Negeri 1 Bangkinang Kota, Jurusan Teknik Pemesinan melalui kegiatan pengabdian kepada masyarakat. Tujuan kegiatan ini adalah untuk meningkatkan kompetensi CAD dari siswa smk menggunakan software Solidworks. Hasil kegiatan pelatihan menunjukkan tingkat keberhasilan dengan indikasi adanya adanya respon yang positif dari peserta serta pemahaman peserta terhadap materi yang diajarkan.